2013
DOI: 10.1007/s00404-013-2762-7
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid suppresses cervical cancer tumor progression possibly via activating Notch1 signaling and enhances receptor-targeted cancer chemotherapeutic via activating somatostatin receptor type II

Abstract: VPA could not only suppress tumor progression but also provide a novel promising therapeutic choice in combination with a receptor-targeted cytotoxic conjugate via activating the specific receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 21 publications
6
26
0
Order By: Relevance
“…For instance, VPA could act as a tumor suppressor and up-regulate the SSTR2 that is highly expressed in cervical cancer Hela cells. Based on this, VPA and the SSTR2-targeted conjugate COL-SST, used at much lower doses, display a much more synergitic effect on cervical cancer Hela tumor growth than did each single one given at higher doses [7,43]. Similar results were also observed with the treatment of VPA and another conjugate CPT-SST in Hela tumors in xenografts [9].…”
Section: Vpa In Combination With Cytotoxic Peptide-drug Conjugatesmentioning
confidence: 73%
See 2 more Smart Citations
“…For instance, VPA could act as a tumor suppressor and up-regulate the SSTR2 that is highly expressed in cervical cancer Hela cells. Based on this, VPA and the SSTR2-targeted conjugate COL-SST, used at much lower doses, display a much more synergitic effect on cervical cancer Hela tumor growth than did each single one given at higher doses [7,43]. Similar results were also observed with the treatment of VPA and another conjugate CPT-SST in Hela tumors in xenografts [9].…”
Section: Vpa In Combination With Cytotoxic Peptide-drug Conjugatesmentioning
confidence: 73%
“…It has been observed that the combination of VPA and the GRPR-targeted CPT-BN conjugate additively suppress in vitro cell proliferation in leukemia MOLT-4, Jurkat cells, osteosarcoma U2OS cells, carcinoid BON cells and CNDT2 cells. We also have observed that the combination of VPA and another SSTR2-targeted CPT-SST conjugate could enhance the cell proliferative suppression in various cancer cells, [9,43]. For instance, VPA could act as a tumor suppressor and up-regulate the SSTR2 that is highly expressed in cervical cancer Hela cells.…”
Section: Vpa In Combination With Cytotoxic Peptide-drug Conjugatesmentioning
confidence: 84%
See 1 more Smart Citation
“…Khanim and colleagues performed a clinical study on patients with acute myeloid leukemia (AML) and indicated that their clinical response to VPA was relevant to the in vivo level of histone acetylation, the proapoptotic genes, and the genes associated with apoptosis. Furthermore, the sensitivity of cell lines derived from hematologic neoplasms to VPA was closely correlated with FOSB expression in vitro (Tsai et al 2013). SMAD4 plays various roles in different stages of PCa.…”
Section: Discussionmentioning
confidence: 98%
“…HDAC inhibition can increase the expression of several genes by accelerating their transcription, which can enhance the innate immune system and lead to suppression of tumor growth. 9,17 VPA alters the expression of various genes involved in the interaction with the cellular immune system, which is known Figure 5. Generation of mouse CIK cells.…”
Section: Discussionmentioning
confidence: 99%